Sistema de previsão para o manejo da ferrugem asiática em soja - Engers, Lana Bruna de Oliveira (2019)
Asian soybean rust is the most important disease in soybean crop, having a high leaf damage potential. The use of disease forecasting systems may reduce the number of fungicide applications to its requirement and thus also reduces costs, risks of severe epidemics and environmental pollution. This work aimed to establish and test a forecasting system for the occurrence of Asian soybean rust in soybean, based on different meteorological variables and fungicide application intervals. The field experiment was carried out at UFFS - Campus Cerro Largo, with a completely randomized factorial design with 2 soybean genotypes, 6 management programs with 3 replications, totaling 36 plots. The genotypes SYN 1561 (no Inox®) and TMG 7363 RR (Inox®) were sown on November 22, 2018 and fungicide applications were performed to control Asian soybean rust, as indicated by the forecasting system for the 6 treatments: Calendarized application every 14 days from R1, control without spray, 11, 9, 7 and 5 severity values calculated. For this calculation, data were obtained in the UFFS - Campus Cerro Largo Automatic Wheather Station. Data were submitted to ANOVA by F test and means compared by Scott-Knott test at 5% probability of error. In the 11SVC and 9SVC treatments two fungicide sprays were performed, in the 7SVC treatment three sprays and in the 5SVC and in the Calendarized four sprays throughout the crop cycle, as the forecast system indicated. The higher area under the disease-progress curve, both in the upper and lower position of evaluation in the canopy, was observed in the control management programs in the no Inox® genotypes and there was no significant difference in the research between management programs and not genotypes. In both the Inox® and the no Inox® genotypes, management programs 9SVC had the highest, showing only two fungicide sprays at the right time allowed.